To determine the missing value in the mapping from the function \( f(x) = x^2 \), we can calculate the values of \( f(x) \) for each \( x \) value given.
The values of \( x \) are:
- \( -2 \)
- \( -1 \)
- \( 0 \)
- \( 1 \)
Now we calculate \( f(x) \) for each of these:
- \( f(-2) = (-2)^2 = 4 \)
- \( f(-1) = (-1)^2 = 1 \)
- \( f(0) = 0^2 = 0 \)
- \( f(1) = 1^2 = 1 \)
Now we can summarize the pairs:
- From \( x = -2 \), \( y = 4 \) (this should be a pair: \( (-2, 4) \))
- From \( x = -1 \), \( y = 1 \) (pair: \( (-1, 1) \))
- From \( x = 0 \), \( y = 0 \) (pair: \( (0, 0) \))
- From \( x = 1 \), \( y = 1 \) (pair: \( (1, 1) \))
The mapping shows the output values \( y \) reaching values \( 0, 1, 4 \). Since both \( -1 \) and \( 1 \) map to \( 1 \), it appears that there are no missing values for the current outputs provided.
To summarize, the complete mapping of the function \( f(x) = x^2 \) from \( x \) to \( y \) based on your input values is:
- \( (-2, 4) \)
- \( (-1, 1) \)
- \( (0, 0) \)
- \( (1, 1) \)
Since no values are missing in the function's mapping presented, all outputs are accounted for. The final output values from \( x \) correspond correctly to \( y = 0, 1, 4 \) as shown in the pairs derived. Thus, there is no missing value in terms of the values corresponding to \( f(x) \). If there was a specific value you were looking for (a misplaced pair or additional context), please clarify!